Literature Review: Gender and water management organisations in Bangladesh - Clement, Floriane (2012)
This literature review was led to inform the project “G3 - Water Governance and Community-based Management”, funded by the Challenge Programme on Water and Food (CPWF). G3 is part of a cluster of project in the Ganges Basin on Community Based Management. The specific objectives of G3 are to understand the different modes and outcomes of water governance in selected polders and the role that communities play in such governance.